Power and Agenda-Setting in Tanzanian Health Policy: An Analysis of Stakeholder Perspectives - Sara Elisa Fischer; Martin Strandberg-Larsen (Kerman University of Medical Sciences, 2016)
Background: Global health policy is created largely through a collaborative process between development agencies and aid-recipient governments, yet it remains unclear whether governments retain ownership over the creation of policy in their own countries. An assessment of the power structure in this relationship and its influence over agenda-setting is thus the first step towards understanding where progress is still needed in policymaking for development. Methods: This study employed qualitative policy analysis methodology to examine how health-related policy agendas are adopted in low-income countries, using Tanzania as a case study. Semi-structured, in-depth, key informant interviews with 11 policy-makers were conducted on perspectives of the agenda-setting process and its actors. Kingdon's stream theory was chosen as the lens through which to interpret the data analysis. Results: This study demonstrates that while stakeholders each have ways of influencing the process, the power to do so can be assessed based on three major factors: financial incentives, technical expertise, and influential position. Since donors often have two or all of these elements simultaneously a natural power imbalance ensues, whereby donor interests tend to prevail over recipient government limitations in prioritization of agendas. One way to mediate these imbalances seems to be the initiation of meaningful policy dialogue. Conclusion: In Tanzania, the agenda-setting process operates within a complex network of factors that interact until a "policy window" opens and a decision is made. Power in this process often lies not with the Tanzanian government but with the donors, and the contrast between latent presence and deliberate use of this power seems to be based on the donor ideology behind giving aid (defined here by funding modality). Donors who used pooled funding (PF) modalities were less likely to exploit their inherent power, whereas those who preferred to maintain maximum control over the aid they provided (ie, non-pooled funders) more readily wielded their intrinsic power to push their own priorities.